A study on the information needs and information-seeking behavior of rural women in Northern Samar - Ortego, Shealtiel Wahini P. (2018)
Information plays an important role in every human activity, and if used properly, could bring about development and change in an individual’s life and in the society. This explains why access to information among all people regardless of socioeconomic and cultural background should be promoted. It bears stressing that people belonging to the disadvantaged sectors of the society such as ethnic minorities and rural dwellers are particularly susceptible to disparities in accessing information.